The ties that fight. Il potere integrativo delle reti online femministe - Pavan, Elena (SocietàMutamentoPolitica, 2021)
With the pervasive spread of digital media, feminist struggles broaden to new spaces of contention where public discourse becomes central both as a territory and as an instrument of the fight. The strategic use of digital platforms expands the networks underpinning feminist initiatives and imbues them with cultural and symbolic resources which, in turn, contribute to protest organization but also to challenge and redefine the narratives that innervate oppressive systems of relations between genders. This article proposes an analytical approach to read more in depth the transformative potential of feminist online networks that derives from the pervasive use of digital media within feminist collective endeavors. It presents and operationalizes the concept of “integrative power” – i.e., the unique ability to join and coordinate a multiplicity of heterogeneous actors in the formation and continuous redefinition of online collective discourses. The integrative power implies a material aspect, related to the construction of relational networks; a social aspect, pertaining the relational choices made by actors; and a semantic aspect, which regards the construction of collective discourses. Each aspect is operationalized by means of social network analysis tools and is illustrated in practice using the example of Take Back The Tech!, a campaign to reclaim information and communication technologies to empower women and other marginalized gender subjectivities.